2017
DOI: 10.21474/ijar01/2891
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Analysis of Breast Lump in a Tertiary Care Hospital.

Abstract: Introduction: Though mostly benign in nature, breast lump can be malignant. Since breast carcinoma is the second most common killer of the female cancer, it is important to detect it at early stage. Our study aimed to analyse histopathology profile of breast lump. Methods: Histopathology samples were received, processed, reported and recorded in the Pathology laboratory at the Department of Pathology, Govt. Medical College Srinagar. Data was analysed for the period of 1 year. Descriptive statistics was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…4 The malignancy rate in our study was 16% comparable to a study done by Mujahid Ahmad Mir et al in 2017 who reported 18.8% cases of malignancy. 5 The commonest lesion was Infiltrating Ductal carcinoma in our study which constituted 62.5% cases of all malignant lesions. Similarly in a study by Vani Dayanand et al in 2015, IDC was the commonest malignant lesion obtained (85.5% of all malignant lesions).…”
Section: Discussionmentioning
confidence: 54%
“…4 The malignancy rate in our study was 16% comparable to a study done by Mujahid Ahmad Mir et al in 2017 who reported 18.8% cases of malignancy. 5 The commonest lesion was Infiltrating Ductal carcinoma in our study which constituted 62.5% cases of all malignant lesions. Similarly in a study by Vani Dayanand et al in 2015, IDC was the commonest malignant lesion obtained (85.5% of all malignant lesions).…”
Section: Discussionmentioning
confidence: 54%
“…The present study noted the frequency of occurrence of hamartoma to be two percent of all lesions. While Mir MA et al [23] reported 0.5% and Forae et al [24] reported 0.3% of Hamartoma. Mastitis was reported in 1.3% of cases in present study and all cases were seen in age group of 31 to 40 years.…”
Section: Discussionmentioning
confidence: 92%